Situação Espacial de Franquias na América do Sul: morfologia e centralidade urbanas em cidades médias da Argentina, Brasil e Chile - Porto Sales, Andréa Leandra [UNESP] (2014)
In the context of urban restructuring, increasingly refined spatial adjustments, oriented by the prevalence of consumption over production, made the medium-sized cities in South America into profit centres for retail companies which have the brand as the main asset: the franchise. They result, as a product, of a organizational model catalysed within economic restructuring, in which the territorial arrangement upon infrastructures and electronic and regulatory devices, increasingly modern and plastic, favors the formation of business links which overlap the territorial planning and attenuate the hierarchy in urban networks. From the analysis of five South American medium-sized cities: the Brazilian, Presidente Prudente, Campina Grande, Passo Fundo; the Argentinian Tandil; and the Chilean Chillán, we verified that franchises have spatial demands which revolve the debate about the centrality, as a category of urban issues at multiple scales. For that reason, we point out their spatial situation as an indicator of urban centrality in South America...